Anti-coking of Yb-promoted Ni/Al2O3 catalyst in partial oxidation of methane. (6th July 2016) - Ding, Chuanmin; Wang, Junwen; Jia, Yanming; Ai, Ganggang; Liu, Shibin; Liu, Ping; Zhang, Kan; Han, Yulin; Ma, Xishun
Abstract: Carbon deposition is urgent issue for the partial oxidation of methane to synthesis gas (POM). To figure out this problem, Ni–Yb/Al2 O3 catalysts with different Ni/Yb ratios were prepared. The structural properties and carbon deposition of catalysts were characterized by XRD, TEM, N2 adsorption, H2 -TPR, NH3 -TPD and TG techniques. The addition of Yb increased the dispersibility of Ni species and improved the interaction with support, thus preventing the growth of Ni nanoparticles, which was favorable to reduce coking. More importantly, the acidity of Ni/Al2 O3 catalyst was reduced due to addition of Yb, which contributes to improving the carbon balance and inhibiting carbon deposition. The Ni–Yb/Al2 O3 catalyst (Ni/Yb = 1) proved to be more active, giving CH4 conversion of 98%, CO selectivity of 98% and H2 selectivity of 83% (800 °C and space velocity of 5 × 10 4 mL g −1 h −1 ). In addition, the addition of Yb was deduced to facilitate adsorption of CO2 and catalyze methane combustion, which was the first step of POM reaction, thus reducing carbon deposition and improving methane conversion. Highlights: Ni–Yb/Al2 O3 catalysts with different Ni/Yb ratios were prepared. The Yb-doping increased metal-support interaction and prevented growth of Ni particles. The reduced acidity of Ni catalyst by Yb-doping contributed to inhibiting coking. The addition of Yb facilitated adsorption of CO2 and catalyzed methane combustion.